2006
DOI: 10.1309/wp59-ym73-l6ce-gx2f
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Unnecessary Inpatient Laboratory Testing in a Teaching Hospital

Abstract: After an inpatient phlebotomy-laboratory test request audit for 2 general inpatient wards identified 5 tests commonly ordered on a recurring basis, a multidisciplinary committee developed a proposal to minimize unnecessary phlebotomies and laboratory tests by reconfiguring the electronic order function to limit phlebotomy-laboratory test requests to occur singly or to recur within one 24-hour window. The proposal was implemented in June 2003. Comparison of fiscal year volume data from before (2002-2003) and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
65
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 22 publications
3
65
1
Order By: Relevance
“…In this case, tests may not be reassessed daily to determine whether they are truly needed. Because our study showed that education and cost awareness were not sufficient to change this ordering practice in residents, an alternative solution could be to modify the ordering system to have an expiration date 8 18. A second explanation is the fact that most ordering in our teaching services is done by interns.…”
Section: Discussionmentioning
confidence: 93%
“…In this case, tests may not be reassessed daily to determine whether they are truly needed. Because our study showed that education and cost awareness were not sufficient to change this ordering practice in residents, an alternative solution could be to modify the ordering system to have an expiration date 8 18. A second explanation is the fact that most ordering in our teaching services is done by interns.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies employing educational interventions to alter clinical behaviour have noted that the long-term effects of any single intervention are often disappointing [2,3,5,6]. Consistent with this, after a few weeks, the rate of pathology testing returned towards baseline rates.…”
mentioning
confidence: 65%
“…In the hospital setting, most test ordering is by junior doctors [6]. There is thus considerable support for strategies targeted at junior medical officers (JMOs) in their first 2 years after graduation, which is recognised as a critical period of training and education [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We need to set standards for the proper testing and the proper frequency of repeating tests, depending on the specialty of medicine and also on the patient's clinical condition and case severity [13]. Then we need to go through suggesting and planning different approaches and methodologies to manage these unnecessary tests, mainly by using health informatics applications and clinical decision support systems, and finally we need to implement such methodologies and measure their short-term as well as long term results in the form of achievable reduction of such tests [14].…”
Section: Introductionmentioning
confidence: 99%